2017
DOI: 10.1111/hex.12620
|View full text |Cite
|
Sign up to set email alerts
|

How do people with long‐term mental health problems negotiate relationships with network members at times of crisis?

Abstract: BackgroundSocial network processes impact on the genesis and management of mental health problems. There is currently less understanding of the way people negotiate networked relationships in times of crisis compared to how they manage at other times.ObjectiveThis paper explores the patterns and nature of personal network involvement at times of crises and how these may differ from day‐to‐day networks of recovery and maintenance.MethodSemi‐structured interviews with 25 participants with a diagnosis of long‐ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…Novel strategies identified in the current study included the active restriction of personal support networks and of non-kin ties in particular especially during periods of acute illness. These findings echo more recent evidence which suggests that network constriction may in fact be an adaptive response which promotes recovery [29,30]. Participants also identified strategies which reflected the flexibility of friendships including diversification or 'thinning' of friendships (e.g.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Novel strategies identified in the current study included the active restriction of personal support networks and of non-kin ties in particular especially during periods of acute illness. These findings echo more recent evidence which suggests that network constriction may in fact be an adaptive response which promotes recovery [29,30]. Participants also identified strategies which reflected the flexibility of friendships including diversification or 'thinning' of friendships (e.g.…”
Section: Discussionsupporting
confidence: 75%
“…Identified network members included friends, family members, health professionals, pets, hobbies, places, activities and objects. This was supplemented by additional questions drawn from the literature which were designed to explore the role and function of different network members in relation to the managing of mental health in everyday settings [29,32,35,[37][38][39]. See also the Appendix.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…SDM in mental health raises further challenges reflecting a context of practice in which patients are aware of the threat or actual containment and coercion [17,18] which necessarily has a bearing on trust, ways of engaging and disclosure to professionals which is likely to impact on the quality of care planning relationships [19]. Additionally, user perspectives on interventions designed to more appropriately meet need have emphasised that they should be readily available and sensitive to community and domestic settings [20], and the context of everyday life which often lies out with the support provided by mental health professionals [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of intervention implementation suggested that severity of disease may impact the level of engagement with the intervention, including the ability to participate in social/community activities. It is possible that study participants with severe disease interpreted the severity of their COPD symptoms as a crisis; withdrawal from social networks and reduced network engagement can occur in a time of crisis, as a form of self-preservation, and avoidance of difficult relational work [29]. Hence, there may be a need for an adapted version of the GENIE intervention where the emphasis for people with a higher need for clinical support is not on expanding networks, but rather on reflection on current level of engagement and on the retention of existing social ties.…”
Section: Discussionmentioning
confidence: 99%